A compact ultra wideba.nd antenna with dual ba.nd-notched design - Jalil Y.E.; Chakrabarty C.K.; Kasi B. (IEEE Computer Society, 2023)
The coexisting issue between ultra-wideba.nd (UWB) system and narrow ba.nd system has been a major concern for quite a while. A filtering property is required in a wideba.nd system in order to avoid the potential interference from other established narrow ba.nd system. Therefore, an UWB antenna with notch ba.nd function is highly sought after to eliminate the interfering signals. This paper presents a compact UWB antenna integrated with dual ba.nd notched and desirable gain characteristics. The proposed antenna consists of an octagon shaped patch with a truncated ground plane that is fed by a 50 ? microstrip line. By inserting two altered H-shaped slots on the proposed radiator, dual ba.nd-notch at the targeted WiMAX frequency ba.nd of 3.3 to 3.6 GHz and WLAN frequency ba.nd of 5.1 to 5.8 GHz are created. The proposed antenna is successfully designed and simulated showing good impedance matching from 2.8 GHz to 11 GHz. Furthermore, the proposed antenna has a compact size of 26 32 mm2. 2013 IEEE.